2020
DOI: 10.1101/2020.07.06.190850
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simple phenotypic tests to improve accuracy in screening chromosomal and plasmid-mediated colistin resistance in gram-negative bacilli

Abstract: ABSTRACTCLSI and EUCAST recommends that only broth microdilution (BMD) should be used for routine colistin susceptibility testing, however, it could be difficult to perform in resource-poor settings. The purpose of this study was to evaluate the accuracy of an agar spot test (COL-AS) and a colistin drop test (COL-DT) as compared to BMD. COL-AS and COL-DT were challenged with a collection of 271 Gram-negative bacilli clinical isolates: 195 Enterobacterales (including 63 mcr-1 po… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…However, the present study demonstrated high sensitivity, specificity, PPV and NPV for detecting colistin resistance. Other study has found comparable outcomes for CA (97.4 %), VME (7.7 %) and ME (0%) [15].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…However, the present study demonstrated high sensitivity, specificity, PPV and NPV for detecting colistin resistance. Other study has found comparable outcomes for CA (97.4 %), VME (7.7 %) and ME (0%) [15].…”
Section: Discussionmentioning
confidence: 61%
“…In our study, we evaluated a larger number of strains (n=309) than previous studies, where the number of strains analysed ranged from 75 to 271 isolates [9,11,14,15,20]. Overall, the drop test met the FDA-established criteria for assessing antimicrobial susceptibility [18].…”
Section: Discussionmentioning
confidence: 99%
“…They established a CA of 98.5% when compared to broth microdilution for Enterobacterales . 18 CAS has been used in the microbiology laboratory system in Argentina since 2018 with excellent results. Giacoboni et al, and Yauri‐Condor et al, in Peru, reported similar results with CAS for Enterobacterales .…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, Pasterán et al described the technique known as Colistin Agar Spot (CAS), based on agar dilution using a single colistin sulfate concentration (3 μg/ml) but with a simplified inoculation (20‐mm drop‐spot of a 0.5 McFarland bacterial suspension). They established a CA of 98.5% when compared to broth microdilution for Enterobacterales 18 . CAS has been used in the microbiology laboratory system in Argentina since 2018 with excellent results.…”
Section: Discussionmentioning
confidence: 99%
“…In the Colistin Agar Spot test, 3.0 μg/mL of colistin is added into melted MHA and subsequently swabbed with a 0.5 McFarland standard suspension of the tested strain within a 1 cm 2 spot. Both methods showed low very major errors rates (0.7%) and major errors rates (~3.7%), but these occurred particularly for the mcr-1 strains [37].…”
Section: Clinical Isolatesmentioning
confidence: 91%